Peran Seni Islam dalam Film Pendek Nussa “Belajar Jujur” Sebagai Media Dakwah Pembinaan Akhlak - Viki Fadhilah; Meti andani; Sri Yulianti; Yazida Ichsan (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2022)
Art education in Islam is very important to be instilled in children, apart from being a medium for conveying the messages implied in it, art in Islam also gives an impression that has elements of beauty and harmony, so there is a need for learning media in improving education through the art of Islamic education. The purpose of this study was focused on fostering students' morals through the short film Nusa Rara entitled